How a 16% Carbamide Peroxide Home Bleaching Agent Affects the Surface Properties of Chairside CAD/CAM Materials? - Serin-Kalay, Tugba; Zaim, Beyza (Odovtos - International Journal of Dental Sciences, 2021)
Surface changes of restorative materials after bleaching have clinical importance in terms of the durability and survival of restorations. This study aimed to evaluate the effect of home bleaching on the surface roughness, microhardness, and surface analysis of four different types of chairside computer-aided design and computer-aided manufacturing (CAD/CAM) materials. Specimens were prepared from composite resin (Brilliant Crios: BC), resin nanoceramic (Lava Ultimate: LU), polymer-infiltrated ceramic-network (Vita Enamic: VE), and zirconia-reinforced lithium silicate glass-ceramic (Vita Suprinity: VS) CAD/CAM materials. Specimens were polished using 800, 1000, 1200, and 2000 grit SiC papers. Each restorative material was randomly divided into two groups; control and bleaching (n=10). The 16% carbamide peroxide bleaching agent (Whiteness Perfect 16%, FGM) was applied to the specimens for 4 h/day for 14 days. Surface roughness values (Ra) were obtained using a profilometer, and microhardness values (VHN) were obtained using a Vickers microhardness test. Surface analysis of specimens was evaluated by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). Data were analyzed Two-way ANOVA and Fisher’s Least Significant Difference (LSD) test (p<0.05). After bleaching, the surface roughness of BC (p<0.001) and VE (p<0.032) significantly increased. Bleaching did not significantly affect the microhardness of CAD/CAM materials. SEM evaluation showed material-dependent surface damages after bleaching procedures. The effect of 16% carbamide peroxide home bleaching agent on surface roughness and microhardness of chairside CAD/CAM materials is material-dependent. Before bleaching, restorative materials should be protected by applying a protective barrier and contact with the bleaching agent should be minimized. Also, after bleaching, the restoration surface should be carefully inspected, and re-polishing might be beneficial.